What are the additional signs and symptoms in patients with detrusor underactivity and coexisting detrusor overactivity?. Issue 7 (10th April 2018) - Gammie, Andrew; Kaper, Mathilde; Steup, Achim; Yoshida, Satoshi; Dorrepaal, Caroline; Kos, Ton; Abrams, Paul
Abstract : Aims: This study aimed to determine what difference the inclusion of patients with coexisting detrusor overactivity (DO) makes to the signs and symptoms of patients with detrusor underactivity (DU). Methods: A total of 250 male and 435 female urodynamic tests were analyzed retrospectively. Signs and symptoms which showed a statistically significant difference between DU without DO and DU with DO were identified. Results: Males with DO in addition to DU had higher age and number of daily micturitions, and were more likely to report urgency with or without urgency incontinence than males with DU without DO. They also had lower volumes for first desire to void, volume voided, and post void residual urine, lower abdominal pressure at Q max and were less likely to report a history of retention or reduced bladder filling sensation than males with DU without DO. Females with DO in addition to DU had higher age and BMI, and were more likely to report urgency incontinence, higher day and night pad usage, constipation and have reduced anal tone than females with DU without DO. They also had lower volumes for first desire to void, volume voided, and post void residual urine, and lower abdominal pressure at Q max than females who had DU without DO. Conclusions: There are differences in signs and symptoms between patients who have DU without DO, compared to patients having DU with DO. This understanding will help future studies investigating treatment options for DU patients.